The Moss flora of Imbak Canyon Conservation area, Sabah - Chua, Mung Seng (2013)
This study was carried out to collect, identify, prepare descriptions, construct keys to species, and to assess general phytogeographical affinities of mosses from Imbak Canyon Conservation Area (ICCA) within Borneo. A total of 674 moss specimens were collected and examined from the study area. From this collection, 177 species, 13 varieties and four subspecies distributed in 68 genera and 27 families of mosses have been identified. This number represents about 26% of the 741 reported mosses from Borneo and about 32% of the 618 mosses in Sabah. The three largest families are Calymperaceae, Sematophyllaceae and Pylaisiadelphaceae, with 40, 31 and 18 species and varieties, respectively. A total of seven species are added to the moss flora of Borneo: Ectropothecium stria tu/um, Fissidens /axitextus, F. pseudoceylonensis, F. serratus, Taxithelium oblongifolium, C/astobryum epiphy/lum and Macromitrium orthostichum. Furthermore, four species are new records to Sabah: Leucobryum sericeum, Papillidiopsis complanata, Mitthyridium crassum and Syrrhopodon scalariformis. The moss flora of ICCA is similar to that of Maliau Basin Conservation Area in terms of species composition. Interestingly, ICCA has two endemic species to Borneo, Syrrhopodon scalariformis and Chaetomitrium maryatii, adding value to this conservation area. In conclusion, the moss flora of ICCA is rich and comparable to other large protected areas in Sabah.